Management of an Infected Vesicourachal Diverticulum in a 42-Year-Old Woman - Maria Erodotou; Maria Isaia; Georgios Fragkiadakis; Theocharis Tontikidis; Kosmas Tyriakidis; Spyridon Palaiologos; Nikolaos Nikolaou (Case Reports in Urology)
Urachal remnant anomalies are uncommon in adults and can be confused with a variety of clinical conditions when symptomatic or infected. Vesicourachal diverticulum is the rarest type, accounting for approximately 3% to 5% of congenital urachal anomalies. We report the case of a 42-year-old female patient, who presented to the emergency department with lower abdominal pain and a palpable abdominal mass. An infected vesicourachal diverticulum was diagnosed after imaging studies and was initially treated with intravenous antibiotic therapy and drainage of the urachal diverticulum to the urinary bladder through a JJ stent. Finally, the patient underwent open surgical excision of the urachal remnant. The postoperative course was uneventful, and the histopathological examination confirmed the diagnosis of vesicourachal diverticulum. We recommend drainage of an infected vesicourachal diverticulum through the bladder by JJ stent placement inside its lumen during cystoscopy, as an alternative to percutaneous drainage reported in the literature.